2008
DOI: 10.1111/j.1365-2699.2008.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Walking with worms: coral‐associated epifaunal nematodes

Abstract: To study the community structure and habitat preferences of the Epsilonematidae and Draconematidae in coral degradation zones. To assess the contribution of different localities and microhabitats to meiobenthic diversity in such ecosystems. To discuss dispersive capacities and the occurrence of cryptic species in meiobenthic organisms. Porcupine Seabight (north-east Atlantic Ocean; continental slope) and a transect along the Kenyan coast (Indian Ocean; shallow lagoon). In the north-east Atlantic, dead coral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…These studies have proven that bio-constructor organisms (as gold corals or deep-water corals), thanks to the complex structure created by their large and hard skeletons, promote benthic biodiversity of hard bottoms by increasing the spatial heterogeneity of the substrate [5], [8], [48], [49]. Recent studies also demonstrated that these corals are able to promote biodiversity even when dead (e.g., coral rubbles), by creating novel substrates [20], [50]. These complex ecosystems are severely threatened by a variety of anthropogenic (e.g., trawling fisheries) and natural disturbances (e.g., climate-driven episodic events, such as dense shelf water cascading and temperature anomalies [15], [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have proven that bio-constructor organisms (as gold corals or deep-water corals), thanks to the complex structure created by their large and hard skeletons, promote benthic biodiversity of hard bottoms by increasing the spatial heterogeneity of the substrate [5], [8], [48], [49]. Recent studies also demonstrated that these corals are able to promote biodiversity even when dead (e.g., coral rubbles), by creating novel substrates [20], [50]. These complex ecosystems are severely threatened by a variety of anthropogenic (e.g., trawling fisheries) and natural disturbances (e.g., climate-driven episodic events, such as dense shelf water cascading and temperature anomalies [15], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Very little information is available on the role of habitat heterogeneity in modulating the biodiversity of soft-bottom sediments surrounding coral-associated habitats [20], [21]. For example, it has been shown that the meiofaunal abundance and biodiversity in proximity of forests of the gold coral Savalia savaglia are significantly higher than soft bottoms at the same depth but without corals.…”
Section: Introductionmentioning
confidence: 99%
“…e occurrence of morphologically identical nematode species in completely divergent habitats ("meiofauna paradox" sensu Giere, [56]) is also common in marine meiofauna. However, the existence of cryptic species (a complex of morphologically identical species which can only be differentiated by DNA) or a parallel evolution in response to similar microhabitats seems to be more plausible explanation to this trend than the dispersal capacities (see for review [41]). erefore, theories on the biogeography of nematodes as well as other meiofaunal groups should be proposed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the sediment grain size appears to be one of the main environmental variables in�uencing the horizontal distribution of nematodes. Different sediment types are characterized by different nematode assemblages and by a predominance of speci�c families, so-called isocommunities or parallel communities (see [4,41,42]). …”
Section: Discussionmentioning
confidence: 99%
“…To date, only the coral reef from the Porcupine Seabight (NE Atlantic) was in-vestigated (Raes and Vanreusel, 2006;Raes et al, 2008). According to this study, Desmoscolex was the dominating genus in the sediments underlying the coral reef, followed by Pselionema, Sabatieria, Acantholaimus and Desmodora.…”
Section: Composition Of Nematode Assemblagesmentioning
confidence: 99%